Impact of inotuzumab ozogamicin on outcome in relapsed or refractory acute B-cell lymphoblastic leukemia patients prior to allogeneic hematopoietic stem cell transplantation and risk of sinusoidal obstruction syndrome/venous occlusive disease - Kayser, Sabine; Sartor, Chiara; Giglio, Fabio; Bruno, Alessandro; Webster, Jonathan; Chiusolo, Patrizia; Saraceni, Francesco; Guerzoni, Selene; Pochintesta, Lara; Borlenghi, Erika; Marconi, Giovanni; Zacheo, Irene; et al. (Haematologica, 2024)
We evaluated 58 patients with relapsed or refractory (r/r) acute B-lymphoblastic leukemia (B-ALL; median age 42.5 years; range, 16-69 years), treated with inotuzumab ozogamicin (INO) between 2016-2022 and who received an allogeneic hematopoietic stem cell transplantation (allo-HCT) consecutively. Forty-seven (81%) of the 58 patients were heavily pretreated receiving intensive chemotherapy +/- tyrosine kinase inhibitor, blinatumomab in 24 (41%) and allo-HCT at first-line in 11 (19%) patients. Complete remission rate prior to allo-HCT was 84%. Median follow-up was 30.5 months and median overall survival (OS) measured from start of INO was 11.2 months. One- and 2-year OS rates were 50% (95% confidence interval [CI]: 38.4-56.1) and 36.7% (95% CI: 25.5-52.9), respectively. Sinusoidal obstruction syndrome/venous occlusive disease (SOS/ VOD) after allo-HCT occurred in 17 (29%) patients. Of those, nine (53%) patients died due to SOS/VOD and multi-organ failure. Two had received >2 INO cycles (3 cycles, 5 cycles, N=1, each), all others ≤2 INO cycles prior to allo-HCT. Logistic regression analysis revealed conditioning with double alkylators (P=0.038) and allo-HCT during first-line therapy (P=0.050) as significant risk factors for SOS/VOD and in trend allo-HCT ≤60 days from last INO application (P=0.07), whereas number of INO cycles before allo-HCT and time between last INO application and allo-HCT were not significant. Relapse/progressive disease occurred in 20 (34%) patients. Of those, five (25%) patients are still alive, whereas 15 succumbed of their disease. Treatment with INO seems to be an effective approach with successful bridge-to-transplant. However, risk of SOS/VOD is high, necessitating continuous monitoring and recognition of SOS/VOD risk factors.